Analisis Kontribusi Pajak Daerah Jakarta Utara Terhadap Penerimaan Pajak Daerah Dki Jakarta - Irene Oktaviani Wijaya, Ngadiman (Jurnal Paradigma Akuntansi, 2019)
This study aims to determine the level of the contribution of hotel tax, restaurant tax, entertainment tax, advertisement tax and parking tax on local tax revenues in Suku Badan Pajak dan Retribusi Daerah Kota Administrasi Jakarta Utara (Period 2012-2016). This research uses descriptive analysis method. The data collection technique is interview and documentation in the form of goals and realizations from the hotel tax, restaurant tax, entertainment tax, advertisement tax and parking tax in Suku Badan Pajak dan Retribusi Daerah Kota Administrasi Jakarta Utara from 2012 until 2016.The results of the study show that the percentage of hotel tax, advertisement tax and parking tax in the North Jakarta area to DKI Jakarta local tax revenues are still in a very less category, which is below 10%, while the contribution of restaurant tax is in the less category with a percentage of 10.10 - 20%, the highest contribution rate is entertainment tax which is in the medium category with a percentage of 20.10 - 30%.